Analisis Pola Pikir Siswa dalam Menyelesaikan Soal Fluida Statis Berdasarkan Tingkat Metakognisi - Zakaria Sandy Pamungkas; Aminah Siti Nonoh; Fahru Nurosyid (Universitas Sebelas Maret, 2019)
This study aims to analyze students mindset in solving a static fluid problem based on metacognition level. This research includes descriptive research. The subject of this research is 99 students of grade XI SMA Batik 2 Surakarta. Data collection methods used are test methods and questionnaires. Data analysis techniques using qualitative descriptive analysis. The results showed that students at the metacognition level of tacit use had a thinking pattern in identifying problems by experimenting based on what was already known, students at the metacognition level of aware use had a thought pattern of identifying problems and representing problems by explaining concepts, students at the metacognition level of strategic use have a mindset of identifying and formulating problems, representing problems and planning solutions for completion by proposing completion measures and students at the reflective use level having a mindset of identifying and formulating problems, representing problems, completion steps and evaluate results and completion by providing reasons for selection of settlement measures.